Project Based Learning dan Contextual Teaching and Learning Serta Gaya Belajar Pada Ilmu Pengetahuan Alam - Lilies Mulyaningsih; Rufi'i Rufi'i; Djoko Adi Walujo (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2021)
The purpose of this study was to determine the effect of the application of learning PBL and CTL on the ability to learn science, to determine the effect of learning styles on the ability to learn science, and to determine the interaction between the application of PBL and CTL learning and learning styles on the ability to learn science. This research method uses experiments with treatment design by level design. The population in this study were 6 classes. The sampling technique is done by simple random sampling by lottery numbers. Data analysis technique used two-way Anava with a significance value of α = 0.05. The results of this study indicate that there is an effect of PBL and CTL learning on science learning abilities, there is no influence of learning styles on science learning abilities, and there is an interaction between PBL and CTL learning and on science learning abilities.